Near-infrared laser-controlled nitric oxide-releasing gold nanostar/hollow polydopamine Janus nanoparticles for synergistic elimination of methicillin-resistant Staphylococcus aureus and wound healing. (15th April 2022) - Liang, Zhuoying; Liu, Wenkang; Wang, Ziqiang; Zheng, Peilian; Liu, Wei; Zhao, Jianfu; Zhong, Yunlong; Zhang, Yan; Lin, Jing; Xue, Wei; Yu, Siming
Abstract: Recently, nitric oxide (NO) has received increasing interest in combat against bacteria-induced infections because of its ability to sensitize and enhance the antibacterial effectiveness of many therapeutic approaches such as antibiotics. However, high-efficient loading and controlled release of NO remain a big challenge. In the present work, a type of gold nanostar/hollow polydopamine Janus nanostructure (GNS/HPDA JNPs) with precise near infrared (NIR)-controlled NO release property was fabricated using a facile seed-mediated method. Upon NIR laser irradiation, the NO-releasing GNS/HPDA JNPs (GNS/HPDA-BNN6) exhibited a synergistic photothermal and NO antibacterial effect by significantly inhibiting the growth and biofilm formation of both Gram-negative and Gram-positive bacterial strains, including methicillin-resistant Staphylococcus aureus (MRSA). An in-depth mechanism study revealed that two pathways were mainly involved in the synergistic photothermal and NO antibacterial effect. In one pathway, the synergistic effect severely destroyed the bacterial membrane by causing leakage of intracellular components such as DNA. In another pathway, the synergistic effect largely disturbed bacterial metabolism by regulating relative metabolic genes, followed by enhancing ROS generation to cause intracellular GSH depletion and DNA damage. More importantly, the synergistic effect significantly diminished the drug resistance of MRSA by downregulating the expression of the drug-resistant gene mecA and some relative multidrug efflux pumps ( e.g., SepA and Tet38 ). An in vivo evaluation using a rat model with MRSA-infected wounds indicated that the synergistic photothermal and NO effect of GNS/HPDA-BNN6 can effectively eliminate MRSA from wounds, thereby alleviating inflammation and promoting wound healing. Statement of significance: Multidrug-resistant (MDR) bacteria have become a big threat to mankind, and therefore, the development of innovative antibacterial agents with high antibacterial efficiency is urgently required. Nanomaterial-mediated nitric oxide (NO) therapy is a promising strategy to effectively combat MDR bacteria through a synergistic antibacterial effect. Here, a gold nanostar/hollow polydopamine Janus nanostructure with precise near infrared (NIR) light-controlled NO release property (GNS/HPDA-BNN6) was developed. Both in vitro and in vivo evaluations demonstrated that GNS/HPDA-BNN6 could effectively eliminate methicillin-resistant Staphylococcus aureus (MRSA) from infected wounds and promote wound healing through a synergistic photothermal and NO therapeutic effect. Remarkably, the synergistic effect significantly diminished the drug resistance of MRSA by downregulating the expression of some drug-resistant genes and multidrug efflux pumps. Graphical abstract: Image, graphical abstract